The moonlighting peroxiredoxin-glutaredoxin in Neisseria meningitidis binds plasminogen via a C-terminal lysine residue and contributes to survival in a whole blood model. (February 2020) - Aljannat, Mahab A.K.; Oldfield, Neil J.; Albasri, Hibah M.; Dorrington, Louise K.G.; Ohri, Radhica L.; Wooldridge, Karl G.; Turner, David P.J.
Abstract: Neisseria meningitidis is a human-restricted bacterium that can invade the bloodstream and cross the blood-brain barrier resulting in life-threatening sepsis and meningitis. Meningococci express a cytoplasmic peroxiredoxin-glutaredoxin (Prx5-Grx) hybrid protein that has also been identified on the bacterial surface. Here, recombinant Prx5-Grx was confirmed as a plasminogen (Plg)-binding protein, in an interaction which could be inhibited by the lysine analogue ε-aminocapronic acid. rPrx5-Grx derivatives bearing a substituted C-terminal lysine residue (rPrx5-Grx K244A ), but not the active site cysteine residue (rPrx5-Grx C185A ) or the sub-terminal rPrx5-Grx K230A lysine residue, exhibited significantly reduced Plg-binding. The absence of Prx5-Grx did not significantly reduce the ability of whole meningococcal cells to bind Plg, but under hydrogen peroxide-mediated oxidative stress, the N. meningitidis Δ pxn5-grx mutant survived significantly better than the wild-type or complemented strains. Significantly, using human whole blood as a model of meningococcal bacteremia, it was found that the N. meningitidis Δ pxn5-grx mutant had a survival defect compared with the parental or complemented strain, confirming an important role for Prx5-Grx in meningococcal pathogenesis. Highlights: Meningococcal Prx5-Grx interacts with plasminogen via a C-terminal lysine residue. Loss of Prx5-Grx does not reduce the ability of meningococci to bind Plg. Loss of Prx5-Grx enhances meningococcal survival under oxidative stress. Loss of Prx5-Grx results in a survival defect in human whole blood.